Developing and Validating a Digital Competence Framework for Pre-service STEM Teachers: Evidence at a Public University in Vietnam - Nguyen Duc Giang; Nguyen Nam Phuong; Nguyen Thi Thanh Hong (International Journal of STEM Education for Sustainability, 2026)
The higher education system in Vietnam has many opportunities and challenges brought about by digital transformation, especially in building excellent human resources. The primary responsibility for building a teaching staff with high moral qualities and meeting the criteria for required competence and adaptability to the needs of the social environment lies with the key pedagogical universities. There are two research objectives that this study aims to resolve: (1) What are the standards and definitions proposed for a framework of digital competency for pre-service Science, Technology, Engineering, and Mathematics (STEM) teachers? (2) What are the basic guidelines that can lead to the assessment of digital competency for STEM students at pedagogical universities? The data was collected from a survey of 945 students from STEM Faculties at a public university in Vietnam using a mixed methods approach, and the reliability index of the measuring scale was determined to be satisfactory. To standardize the scale and integrate it into the learning objectives of teacher education programs at pedagogical universities, this study offers recommendations for future studies.